Robust decision-making under risk and ambiguity - Maximilian Blesch; Philipp Eisenhauer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Economists often estimate a subset of their model parameters outside the model and let the decision-makers inside the model treat these point estimates as-if they are correct. This practice ignores model ambiguity, opens the door for misspecification of the decision problem, and leads to post-decision disappointment. We develop a framework to explore, evaluate, and optimize decision rules that explicitly account for the uncertainty in the first step estimation using statistical decision theory. We show how to operationalize our analysis by studying a stochastic dynamic investment model where the decision-makers take ambiguity about the model's transition dynamics directly into account.
Keywords: D81; C44; D25; 330; decision-making under uncertainty; robust Markov decision process